Tomato as Potential Source of Natural Additives for Meat Industry. A Review - Rubén Domínguez; Patricia Gullón; Mirian Pateiro; Paulo E. S. Munekata; Wangang Zhang; José Manuel Lorenzo (Antioxidants, 2020)
Tomato industry produces huge amounts of by-products that represent an environmental and economic problem. However, these by-products contain multiple bioactive compounds, which would make them a renewable source for obtaining natural antioxidants and colourants (carotenoids). This is in line with the preferences of the current consumer who demands more natural and healthy products. However, the lipophilic character of carotenoids means that their extraction must be carried out using toxic organic solvents. To overcome environmental and health problems of organic solvents, the application of supercritical fluid extraction (SFE) for the extraction of lipophilic compounds such as lycopene was used successfully, achieving yields similar to those obtained with conventional techniques. Nonetheless, the extraction conditions must be carefully selected, to obtain high yields and at the same time maintain a high antioxidant capacity. On the other hand, the use of tomato and tomato extracts as natural additives in meat products are reduced in comparison with other natural antioxidant/colourant extracts. However, different researches conclude that the use of tomato improved nutritional quality, reduced lipid oxidation and increased stability during the shelf-life period of meat products, while retaining or increasing sensory properties and overall acceptability, which converts tomato by-products into a promising source of natural additives.